The Effect of Discovery-Based Blended Learning towards Learning Performance of High School Students in Linear Motion - Odja, Abdul Haris; Lestari, Wiwin; Payu, Citron Supu (FKIP Universitas Lampung, 2022)
This study aims to determine the effect of the application of the video-assisted discovery learning model that is implemented with blended learning on the concept of straight motion in high school. This research was conducted at SMA Negeri 1 Kabila using the experimental method and the One-Group Pretest-Posttest Design. This design has a pretest before being given treatment and a posttest after being given treatment. From the N-gain test data, the average pretest value is 5.30 and the posttest average value is 76.30. The normalized N-gain value is 0.75 in the high category. Hypothesis testing on the data obtained tcount of 58.13 while the value of ttable at a significance level of 5% is 2.03452. Thus tcount > ttable So it can be concluded that there is an effect of student learning outcomes after the application of the discovery learning learning model assisted by video implementation of blended learning on the concept of straight motion in high school Keywords: blended learning, discovery learning, high school students. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp385-391